2007
DOI: 10.1111/j.1365-2982.2007.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter of Oddi function in the Australian brush‐tailed possum is inhibited by intragastric ethanol

Abstract: The role of sphincter of Oddi (SO) function in alcoholic acute pancreatitis (AP) is unclear. We aimed to compare the effect of i.v. and intragastric (IG) ethanol on SO function (i.e. trans-sphincteric flow; TSF) and investigate possible neural mechanisms. The involvement of gastric mucosal damage was also investigated by pretreatment with pantoprazole. In anaesthetized Australian possums, blood pressure (BP), TSF and blood ethanol concentrations were measured after i.v. or IG ethanol. Possums were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Why drinkers are more likely to require cholecystectomy than other persons with gallstones is unknown. However, some studies demonstrated that ethanol decreased activity of the sphincter of Oddi . Such sphincteric dysfunction might increase risk of symptomatic gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Why drinkers are more likely to require cholecystectomy than other persons with gallstones is unknown. However, some studies demonstrated that ethanol decreased activity of the sphincter of Oddi . Such sphincteric dysfunction might increase risk of symptomatic gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Obserwowane u osób przewlekle pijących alkohol spowolnienie motoryki jelitowej naraża je na nadmierny rozwój flory jelitowej, zwiększoną produkcję aldehydu octowego i translokację bakteryjną [72][73][74][75][76][77][78][79]. Nadmiar toksycznego aldehydu octowego wiąże się z białkami komórkowymi, co osłabia potencjał antyoksydacyjny, a tym samym odporność błony śluzowej.…”
Section: Wpływ Napojów Alkoholowych Na Jelito Cienkieunclassified
“…Furthermore, interesting animal studies have demonstrated that ethanol may have direct effects on the pancreas, such as microcirculatory changes and direct toxic damage to the pancreatic acini [ 22 - 24 ]. Moreover, the mechanism of ethanol-induced pancreatitis has been well-studied in an interesting animal model in which it was demonstrated that sphincter of Oddi dysfunction was implicated in several forms of acute and chronic pancreatitis [ 25 ]. In fact, according to the authors, since trans-sphincteric flow, regulated by the sphincter of Oddi which acts as a pump, is a direct measure of sphincter of Oddi function, an alteration of this trans-sphincteric flow after intragastric or i.v.…”
Section: Reviewmentioning
confidence: 99%
“…In fact, according to the authors, since trans-sphincteric flow, regulated by the sphincter of Oddi which acts as a pump, is a direct measure of sphincter of Oddi function, an alteration of this trans-sphincteric flow after intragastric or i.v. ethanol may indicate Oddi dysfunction; the authors also investigated whether neural mechanisms and gastric mucosal damage might play a role in this process [ 25 ], demonstrating that both intragastric and i.v. ethanol administration altered the Oddi trans-sphincteric flow.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation